Synthesis, Thermal Analysis, and Thermodynamic Properties Study of New Quinoline Derivative and Their V(IV), Co(II), and Cu(II) Complexes - Raghad Jawad Kadhim Aldoghachi; Faris Abdulridha Jassim Aldoghachi; Tahseen Abdul Qader Alsalim; Mohd Lokman Ibrahim (Universitas Gadjah Mada, 2022)
A new ligand (E)-2-((2-chloro-6-methylquinoline-3-yl)methylene)-N'-((E)-(2-chloro-6-methylquinoline-3-yl)methylene)hydrazine-1-carbothiohydrazide (QH) was prepared by reacting hydrazine hydrate with carbon disulfide to yield thiocarbohydrazide. The thiocarbohydrazide in the second step was treated with a quinoline derivative 2-chloro-6-methylquinoline-3-carbaldehyde to yield the ligand. The ligand was identified by spectroscopic techniques FTIR, 1H-NMR, and 13C-NMR. Next, vanadium (V), cobalt (Co), and copper (Cu) complexes were prepared in the [M:L] ratio of 1:1 (QV, QCo, QCu). The complexes were characterized using FTIR, ESI, magnetic susceptibility, and molar conductivity. The thermal analysis (TGA) of V(IV), Co(II), and Cu(II) complexes were studied. The activation thermodynamic parameters, such as the energy of activation, enthalpy, entropy, and free energy change of the complexes, were evaluated, and the stabilities of the thermal decomposition of the complexes were discussed.